Real options analysis applied to investment projects in planted forests of Pinus - Simões, Danilo [UNESP]; Rocha, Qüinny Soares [UNESP]; Munis, Rafaele Almeida [UNESP]; Da Silva, Richardson Barbosa Gomes [UNESP]; Garcia, Giovani Caprioli [UNESP] (CIRAD (Centre de Cooperation Internationale en Recherche Agronomique Pour le Developpement), 2022)
Planted forests are long-term projects involving a large monetary contribution, and generally require the incorporation of managerial flexibility. As the traditional methodology for economic evaluation does not allow for the incorporation of these flexibilities, our study aimed to analyze whether investment projects in planted forests of Pinus elliottii Engelm. are economically feasible, by applying a real options analysis. We used empirical data from one hectare of a planted forest of P. elliottii with a 14-year planning horizon. Managerial flexibilities were incorporated in combinations and also separately, as options to defer, expand or abandon the investment project. Through Monte Carlo simulation, the present value of USD 1.016 was conditioned to anticipated return values from the second to the fourteenth year, with a volatility return of 14.5%. With real options analysis, the value of the combined options was USD 29, which, in terms of traditional net present value, showed an expanded net present value of USD 468. The real options analysis thus shows that investment projects in planted forests of P. elliottii are economically feasible. Given that real options analysis is a methodology not widely used in the forestry sector for economic analysis of investment projects, this study can be used to assist forest managers in analysing investment risks and decisions, specifically those related to market fluctuations of planted forests of Pinus spp., assuming that the real options of deferral, expansion and abandonment of an investment project are used.
Análisis de opciones reales aplicadas a proyectos de inversión en plantaciones forestales de Pinus
Analyse des options réelles appliquée aux projets d’investissement dans les forêts plantées à Pinus
Keywords: Brazil; combined options; expanded net present value; forest economy; managerial flexibility; risk management; silviculture